Ternary spreading and the OCP in Copperbelt Bemba - Lee S. Bickmore (LibraryPress@UF, 2013)
Bemba tonology has been described with respect to two prominent claims: H tone local spreading is binary, and is blocked by the OCP. These claims are based on Bemba, as spoken in Northern Zambia. This paper examines these two claims with respect to contemporary Bemba as it is spoken today in the Copperbelt province of Zambia. This paper shows that in Copperbelt Bemba (CB), these two aspects of H tone spreading are markedly different. In CB, local spreading is ternary, not binary, and a H will undergo binary spreading even if it causes an OCP violation. Ternary spread will be shown to follow from two rules: High Tone Doubling and Secondary High Doubling motivated by different constraints within CB tonology. In addition to documenting and describing the behavior of high tone in CB, a comparison to other cases of ternary spreading is also made.